Labour education for 2001 - Bruce Spencer (Adult Education Research Conference, 1996)
How should unions educate their members and activists for the new century ? Labour education trends in the USA, Canada, Britain (UK), Australia, and New Zealand (NZ) indicate that both incorporatist and independent educational strategies will prevail.